Perbandingan Tingkat Penerimaan Pasien Anak Penggunaan Chloride Ethyl Dan Benzocaine Gel Dalam Pencabutan Gigi Susu Berdasarkan Facial Image Scale - Emma Krisyudhanti (Politeknik Kesehatan Kemenkes RI Jakarta I, 2018)
BACKGROUND: Tooth extraction needs to be done to prevent tooth eruption from growing in an incorrect place. If this is left unchecked it will cause malocclusion (tooth structure that is not good and right) which results in the emergence of caries, tartar, bad breath to joint disorders TMJ (Pratiwi, 2009). Before performing tooth extraction, anesthesia needs to be done first. When extraction is generally given local anesthesia, in certain circumstances general anesthesia is performed by an anesthetist. Various types of topical anesthetic ingredients according to the ingredients of the medicine are chloride ethyl, Xylestesin ointment, Xylocain Ointment, Xylocain Spray, and benzocaine (liquid, gel, spray). The level of child acceptance of the dental extraction anesthesia procedure can be measured by the